Synthesis, Characterization and Electrochemical Behaviour of One-dimensional Cu(II) Polymer [Cu(C16H14N2O3)+H2O]n - LI, XUE-MEI; WANG, WEI; MENG, XIANG-TAO; ZHANG, SHU-SHENG (Asian Journal of Chemistry, 2010)
A new complex of catena-poly[μ-N-salicylidene-p-methylphenoxyacetylhydrazino- κ4 O,N,O':N'-copper(II)] was synthesized and characterized by X-ray crystallography and thermal analysis methods. The compound crystallizes in the tetragonal system, space group P-421c, with cell dimensions of a = b = 1.9866(3) nm, c = 0.9097(2) nm, V = 3.590(1) nm3, and Z = 8. The title compound consists of [Cu(sal-mpah)] coordination units (sal-mpah = salicylidene-p-methyl-phenoxyacetylhydrazino) and free water molecules. The Cu(II) ion adopts a distorted square planar geometry. The sal-mpah ligand acts as a μ4-bridge connecting Cu atoms into chains along the c direction. The electrochemical experimental results indicate that [Cu(C16H14N2O3)·H2O]n can bind to DNA by intercalative binding.